Peningkatan Kualitas Air Bersih Sumur Gali Menggunakan Teknologi Filtrasi - Al Kholif, Muhammad; Putra, Muhammad Uke Dwi; Sutrisno, Joko; Sugito, Sugito; Majid, Dian; Nurhayati, Indah (Jurnal Sains dan Teknologi Lingkungan, 2024)
The most common problem encountered in the use of well water is the presence of metal contaminants, particularly iron (Fe) and manganese (Mn). One alternative solution is the use of filtration with zeolite and activated carbon. This research aims to improve the quality of well water by reducing Fe, Mn, and turbidity levels using filtration technology. The treatment reactor consists of two reactors with the difference between reactors 1 and 2 lies in the type of media used. Reactor 1 uses zeolite media, and reactor 2 uses activated carbon. The filtration column used is a PVC pipe with a diameter of 10 cm and a length of 1 m. The independent variable in this study is the composition of the filtration media, consisting of a combination of quartz sand-zeolite and quartz sand-activated carbon. The research findings show that in reactor 1, the decrease in Fe levels from the first day to the third day is 0.4975 mg/L, 0.6175 mg/L, and 0.605 mg/L, whereas in reactor 2, it is 0.9175 mg/L, 0.7725 mg/L, and 0.685 mg/L. The decrease in Mn levels in reactor 1 over three consecutive days is 0.08 mg/L, 0.07 mg/L, and 0.05 mg/L, while in reactor 2, it is 0.12 mg/L, 0.09 mg/L, and 0.06 mg/L. The decrease in turbidity levels in reactor 1 consecutively is 20.825 NTU, 13.305 NTU, and 11.09 NTU, while in reactor 2, it is 21.4775 NTU, 18.36 NTU, and 12.23 NTU. These filtration results have met the clean water quality standards according to PERMENKES No. 32 of 2017.